The Effect of Unemployment and Gross Regional Domestic Product on Inflation in South Sulawesi Province - Firdha Baharuddin (Pustaka Digital Indonesia, 2022)
This study aims to determine whether there is an effect of unemployment and Gross Regional Domestic Product on inflation in South Sulawesi. This research uses quantitative research and the data is processed according to the needs of the model used. The data processing technique uses multiple linear regression through SPSS 22. The data used is secondary data originating from historical records or reports arranged in published and unpublished archives. Controlled inflation is a success in the economy, but it must also be balanced with other economic activities such as lowering interest rates, so that it will increase investment and also spur to increase exports. Increased investment can also increase existing employment opportunities so that unemployment can be reduced. In addition, the government should also re-establish its tax policy. With high taxes, the people's purchasing power becomes weak and will weaken the people's ability to spend Unemployment is not positive and significant as evidenced by a significant value of 0.711 <0.05 where 0.711> from 0.05, which means that unemployment is not related to the inflation rate , this is different from the theory presented by AW Philips (If unemployment is high, inflation is low and vice versa if unemployment is low, inflation is high). The coefficient of the GRDP variable in the multiple regression equation is -1.544, this figure means that if the GRDP variable increases, it will increase inflation. This has a significant and positive effect because the higher the inflation, the GRDP price also increases where goods and services also increase in line with inflation and vice versa. if GRDP increases, inflation will automatically increase, as evidenced by Sig 0.006 <0.05.